The Saint of Incipient Insanities - Shafak, Elif (New York Farrar , Straus and Giroux, 2004)
Follows the adventures of three young Turks loose in America as they negotiate their desires in a land that seems to allow limitless indulgences
Keywords: Immigrants -- Young adults -- Students, Foreign